Efficacy of Methotrexate on Rat Knee Osteoarthritis Induced by Monosodium Iodoacetate - Yamanashi Y; Ohmichi M; Ohmichi Y; Ikemoto T; Arai YC; Maruyama Y; Otsuka S; Hirai S; Naito M; Deie M (Dove Medical Press, 2021)
Yuki Yamanashi,1,* Mika Ohmichi,2,3,* Yusuke Ohmichi,2,3 Tatsunori Ikemoto,1 Young-Chang Arai,4 Yohei Maruyama,3 Shun Otsuka,3 Shuichi Hirai,3 Munekazu Naito,3 Masataka Deie1 1Department of Orthopedic Surgery, Aichi Medical University, Nagakute, Aichi, Japan; 2Department of Anatomy II, Kanazawa Medical University, Kahoku, Ishikawa, Japan; 3Department of Anatomy, Aichi Medical University, Nagakute, Aichi, Japan; 4Institute of Physical Fitness, Sports Medicine and Rehabilitation, Aichi Medical University, Nagakute, Aichi, Japan*These authors contributed equally to this workCorrespondence: Yusuke OhmichiDepartment of Anatomy II, Kanazawa Medical University, Kahoku, Ishikawa, JapanEmail ohmy@kanazawa-med.ac.jpTatsunori IkemotoDepartment of Orthopedic Surgery, Aichi Medical University, Nagakute, Aichi, JapanEmail tatsunon31-ik@umin.ac.jpObjective: To explore whether methotrexate (MTX) prevents joint destruction and improves pain-related behaviors in the acute phase of knee osteoarthritis (OA) induced by monosodium iodoacetate (MIA) in a rat model.Methods: Twenty of 25 male Wistar rats (10– 14 weeks old) received 3 mg MIA via intra-articular injection into their right knee and were then administered a vehicle control (n=10) or 3 mg/kg MTX orally weekly (n=10). We assessed differences in pain-related behavior, spontaneous lifting behavior, micro-computed tomography (CT), histopathology, and expression of pain- and inflammatory-related genes using reverse transcription-quantitative polymerase chain reaction (RT-qPCR) between the two groups for 4 weeks. Five rats were used as untreated controls to assess pain- and inflammatory-related mRNA expression in the dorsal root ganglia (DRG) and knee joints using RT-qPCR.Results: Joint destruction and mechanical hyperalgesia were observed in the vehicle group. Decreases in mechanical pain thresholds for the knee joint and calf muscles were improved after MTX administration; however, joint damage assessed by micro-CT and histopathology was not significantly inhibited by MTX administration, while upregulation levels of transient receptor potential cation channel, subfamily V, member 1 (TRPV-1) (P< 0.01) and brain-derived neurotrophic factor (BDNF) (P=0.02) mRNA in the DRG and nerve growth factor NGF mRNA (P=0.03) in the affected knee joints were significantly suppressed in the MTX group compared with the vehicle group at week 4.Conclusion: Our results imply that MTX administration improves pain-related behaviors and suppresses expression of pain-related mRNAs in the DRG and knee joint; however, MTX is not expected to prevent cartilage degeneration in MIA-induced OA in rat knee.Keywords: knee osteoarthritis, methotrexate, monosodium iodoacetate, inflammation